53BP1 is a novel regulator of angiogenesis in breast cancer. Issue 11 (5th September 2013) - Li, Xiaoyan; Kong, Xiangnan; Wang, Yang; Yang, Qifeng
Abstract : In our previous study, we found that 53BP1 was a tumor suppressor and was associated with prognosis in breast cancer. However, little is known about its role in angiogenesis. In the present study, we aimed to reveal the role of 53BP1 in angiogenesis of breast cancer. With RNA interference and ectopic expression strategies to elucidate the detailed function of 53BP1 in angiogenesis, we observed that ectopic expression of 53BP1 inhibited cellular angiogenesis and 53BP1 RNA interference led to an increase in angiogenesis both in vitro and in vivo . In clinical breast cancer samples, 53BP1 was inversely correlated with CD31, MMP‐2 and MMP‐9 by immunohistochemistry analysis. Furthermore, we showed that the Akt pathway was involved in the antiangiogenesis function of 53BP1 . Overall, our findings demonstrate that 53BP1 plays a vital role in inhibiting angiogenesis. These findings suggest that 53BP1 might provide a viable target therapy for breast cancer.